Assessment of the Supply Chain Management and Problems of Agricultural Production Development and Marketing in Kazakhstan - Samazhan Y.Umirzakov; Asylbek Zh.Nauryzbayev; Akmaral Zh.Bukharbayeva; Dana A.Bekesheva; Ayzhan K.Oralbayeva (International Journal of Supply Chain Management, 2019)
The article deals with the supply chain management of development of agricultural production and marketing. At the same time, an assessment of the agrarian policy pursued is given, recommendations are made to solve the problems of agricultural production and the processing industry, and to improve agriculture in technical support. As well, the article examines the problems of production and sale of agricultural products, analyzes the effectiveness and disadvantages of the programs provided by the state to the development of agricultural production.